Pengaruh Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Mandiangin Batubara - Elza Oktariani Oktariani; Fauziah Afriyani; Emida Emilda (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of the physical work environment and work discipline on employee performance at PT. Mandiangin Batubara, which is located in the Musi Banyuasin District, Tungkal Jaya District, Suka Damai Mandiangin Batubara (MBB) Village. This sample took 50 respondents, using saturated sampling method. This study uses a quantitative descriptive method, the analysis used is multiple linear regression analysis with the t test and f test and the coefficient of determination with the help of SPSS 21. The research results obtained based on the regression Y = 1.938 + 0.062 X1 + 0.702 X2 + e. And it was found that simultaneously the variables of the physical work environment and work discipline affect the performance of employees of PT. Mandiangin Batubara, where the calculated F value = 59.128 > F table with a significant level of 0.000 <0.05. The coefficient of determination of 0.716 means that the magnitude of the influence of the physical work environment and work discipline on employee performance at PT. Mandiangin Batubara is 71.6% with the remaining 28.4% influenced by other variables outside the research, so there is a positive and significant influence of the physical work environment and work discipline on employee performance at PT. Mandiangin Batubara. Based on the results of the research conducted, the results of the first linear regression analysis prove that the physical work environment has an effect on employee performance, which means that H1 is accepted. The second result proves that work discipline affects employee performance, which means that H2 is accepted. Keywords: Work Discipline, Employee Performance and Physical Work Environment